Enhancing Elementary Students’ Numeracy through the GASING Method: A Quasi-Experimental Study - Yessika Destiana Lahabu; Wadan Y Anuli; Shilfany Putri; Mahmud Arif; Sigit Prasetyo; Abroto Abroto (AL-ISHLAH: Jurnal Pendidikan, 2025)
Numeracy competence is a foundational skill for elementary students, essential for success in 21st-century learning. However, many Indonesian students continue to face difficulties in understanding mathematical concepts and performing calculations effectively. This study investigates the effectiveness of the GASING (Gampang, Asyik, Menyenangkan) method in enhancing numeracy skills among fourth-grade students. A quasi-experimental one-group pre-test and post-test design was employed with a mixed-methods approach. Thirty fourth-grade students at MIN 1 Manado participated in the study over two months. Quantitative data were gathered through numeracy tests, while qualitative data were collected via observations, interviews, and open-ended questionnaires. Data were analyzed using paired sample t-tests and thematic coding. Students’ numeracy scores improved significantly from a mean of 45.6 (pre-test) to 78.3 (post-test), with a large effect size (Cohen’s d = 2.63). Observations showed increased engagement and participation, while qualitative feedback revealed reduced math anxiety and increased motivation. Both students and teachers expressed positive perceptions of the method’s interactive and enjoyable approach. The findings suggest that the GASING method effectively improves both computational fluency and conceptual understanding in mathematics. Its emphasis on progressive learning, visual tools, and enjoyable activities fosters a positive learning environment. While the absence of a control group limits generalizability, the results indicate that GASING holds promise as an instructional strategy in elementary numeracy education.